Glycocalyx Damage Within Human Liver Grafts Correlates With Graft Injury and Postoperative Graft Function After Orthotopic Liver Transplantation. Issue 1 (January 2020) - Schiefer, Judith; Faybik, Peter; Koch, Stefan; Tudor, Bianca; Kollmann, Dagmar; Kuessel, Lorenz; Krenn, Claus G.; Berlakovich, Gabriela; Baron, David M.; Baron-Stefaniak, Joanna
Abstract : Background: Destruction of the endothelial glycocalyx has been observed within lung and kidney grafts during ischemic organ preservation. We aimed to quantify glycocalyx damage within human liver grafts after organ preservation and correlate the results with graft injury and postoperative graft function in patients undergoing orthotopic liver transplantation (OLT). Methods: Syndecan-1 (Sdc-1) was measured as indicator of glycocalyx degradation in effluents of 38 liver grafts and serum of patients undergoing OLT. Effluent Sdc-1 concentrations were correlated with hepatic injury markers from the effluent. Furthermore, we assessed the association of Sdc-1 with early allograft dysfunction (EAD), 1-year graft survival, and 1-year patient survival. Results: Effluent Sdc-1 concentrations correlated with effluent concentrations of hepatocellular injury markers, including alkaline phosphatase ( R = 0.543, P = 0.003), aspartate aminotransferase ( R = 0.420, P = 0.029), and lactate ( R = 0.574, P = 0.002). Sdc-1 effluent concentrations were greater in patients who developed EAD compared with those without EAD (4720 [4374–5133] vs 3838 [3202–4240] ng/mL, P = 0.015). Furthermore, receiver operating characteristics analyses revealed that effluent Sdc-1 concentrations (AUC = 0.82, P = 0.017) and serum Sdc-1 concentrations (AUC = 0.84, P = 0.006) were associated with the development of EAD. These results were confirmed by regression analyses. No association was found between Sdc-1 and 1-year graft survival or 1-year patient survival. Conclusions: Our data suggest that the glycocalyx is damaged within human liver grafts during preservation and the extent of glycocalyx damage correlates with the severity of hepatocellular injury. Recipients of livers grafts with greater glycocalyx damage might be at higher risk for development of EAD after OLT. Abstract : Supplemental Digital Content is available in the text.